Ekphrasis, Intertextuality and the Role of the Reader in Poems by Francisco Brines and Claudio Rodríguez - W. Michael Mudrovic (Studies in 20th & 21st Century Literature, 1990)
Ekphrasis, the verbal representation of visual art, affords a singular perspective on a discrepancy between the general conception of intertextuality and its practical application. Francisco Brines's "Museo de la Academia" ("Museum of the Academy") and Claudio Rodríguez's "Hilando" ("Spinning") both contain the description of a painting. Each poet achieves diverse effects with a different handling of the respective paintings, yet both come to surprisingly similar conclusions with regard to the poetic act. Brines's depiction of the martyrdom of St. Sebastian supplies a limited amount of information that dovetails neatly with the use of metaphor and metonymy. Rodríguez's use of synecdoche in conjunction with the description of the dominant figure in Velázquez's The Spinners introduces an overwhelming abundance of allusions that interconnect with one another, weaving the fabric of the text while at the same time unravelling it. Whereas Brines emphatically reminds the reader of the frame separating the participant from the work of art, Rodríguez dissolves it and conflates the world of the text with that of the participant. These variant approaches to the intertextual space correspond to the concept of supplementarity and allow us to deconstruct the commonly-held contradiction between the general and practical acceptations of intertextuality. These two poems also make the metapoetic dimension of the text, the indeterminacy of language, the interrelationship between art and life, and the view of the poem as epistemological and ontological construct—important characteristics of post-Civil War Spanish poetry—stand out in sharp relief. In these poems by major figures of that era ekphrasis leads to the discovery of essential aspects of the reading process and amends our view of intertextuality.
Keywords: Ekphrasis; verbal representation; visual art; art; intertextuality; Francisco Brines; Museo de la Academia; Museum of the Academy; Claudio Rodríguez; Hilando; Spinning; description; painting; poet; effects; effect; poetic act; martyrdom; St. Sebastian; metaphor; metonymy; Rodríguez; synecdoche; dominant figure; dominant; Velázquez; The Spinners; allusions; allusion; interconnect; weaving; fabric; unravelling; Brines; participant; intertextual space; contradiction; general; practical; acceptation; poems; metapoetic; dimension; indeterminacy; language; interrelationship; epistemological; ontological; construct; post-Civil War Spanish poetry; ekphrasis